Doctor? Who? Nurses, patient's best interests and treatment withdrawal: when no doctor is available, should nurses withdraw treatment from patients? - Birchley, Giles (Nursing philosophy, 2013)
Where a decision has been made to stop futile treatment of critically ill patients on an intensive care unit - what is termed withdrawal of treatment in the UK - yet no doctor is available to perform the actions of withdrawal, nurses may be called upon to perform key tasks. In this paper I present two moral justifications for this activity by offering answers to two major questions. One is to ask if it can be in patients' best interests for nurses to be the key actors in withdrawal of life-sustaining treatment. The other is to ask if there is any reason that the nursing profession should not undertake such tasks if this is so. Both these questions require the resolution of weighty moral and philosophical issues. Thus, while offering a serious attempt to provide moral justifications for nurses undertaking withdrawal, this paper also invites debate over both the aim of task division between nurses and doctors, and how we might decide what is in the best interests of patients.